Anthocyanins Activate Membrane Estrogen Receptors with Nanomolar Potencies to Elicit a Nongenomic Vascular Response Via No Production - Garcia Huidobro-Toro, J; Calfio-Painemal, C (American Heart Association Inc., 2021)
BACKGROUND: The vascular pharmacodynamics of anthocyanins is only partially understood. To examine whether the anthocyanin-induced vasorelaxation is related to membrane estrogen receptor activity, the role of ERα or GPER antagonism was ascertained on anthocyanins or 17-β estradiol-(E2) induced vasodilatations and NO production. METHODS AND RESULTS: The rat arterial mesenteric bed was perfused with either anthocyanins or corresponding 3-O-glycosides, or E2, to examine rapid concentration-dependent vasorelaxations. The luminally accessible fraction of NO in mesenteric per-fusates before and after anthocyanins or E2 administration was quantified. Likewise, NO-DAF signal detected NO production in primary endothelial cells cultures incubated with anthocyanins or E2 in the absence and presence of ERα (ICI 182,780) or GPER (G-36) selective antagonists. Anthocyanins or corresponding glycosides elicited, within minutes, vasodilation with nanomolar potencies; half maximal anthocyanin response reached 50% to 60% efficacy, in contrast to acetylcholine. The vasorelaxation is of rapid onset and exclusively endothelium-dependent; NOS inhibition annulled the vasorelaxation. The del-phinidin vascular response was not modified by 100 nmol/L atropine but significantly attenuated by joint application of ICI plus G-36 (52±4.6 versus 8.5±1.5%), revealing the role of membrane estrogen receptors. Moreover, the anthocyanin or E2-induced NO production was antagonized up to 70% by these antagonists. NO-DAF signal elicited by anthocyanins was annulled by NOS inhibition or by ICI plus G-36 addition. CONCLUSIONS: The biomedical effect of anthocyanins or 3-O-glycosylates derivatives contained in naturally purple-colored foods or berries is due to increased NO production, and not to the phytochemical’s antioxidant potential, highlighting the nutraceutical role of natural products in cardiovascular diseases. © 2021 The Authors. Published on behalf of the American Heart Association, Inc., by Wiley.
Keywords: anthocyanins; endothelium; GPER and ER alpha; NO production; nongenomic steroidal actions; vasodilation